Landscape of somatic mutations in sporadic GH-secreting pituitary adenomas. Issue 3 (March 2016) - Ronchi, Cristina L; Peverelli, Erika; Herterich, Sabine; Weigand, Isabel; Mantovani, Giovanna; Schwarzmayr, Thomas; Sbiera, Silviu; Allolio, Bruno; Honegger, Jürgen; Appenzeller, Silke; Lania, Andrea G; Reincke, Martin; et al.
Abstract : Context: Alterations in the cAMP signaling pathway are common in hormonally active endocrine tumors. Somatic mutations at GNAS are causative in 30–40% of GH-secreting adenomas. Recently, mutations affecting the USP8 and PRKACA gene have been reported in ACTH-secreting pituitary adenomas and cortisol-secreting adrenocortical adenomas respectively. However, the pathogenesis of many GH-secreting adenomas remains unclear. Aim: Comprehensive genetic characterization of sporadic GH-secreting adenomas and identification of new driver mutations. Design: Screening for somatic mutations was performed in 67 GH-secreting adenomas by targeted sequencing for GNAS, PRKACA, and USP8 mutations ( n =31) and next-generation exome sequencing ( n =36). Results: By targeted sequencing, known activating mutations in GNAS were detected in five cases (16.1%), while no somatic mutations were observed in both PRKACA and USP8 . Whole-exome sequencing identified 132 protein-altering somatic mutations in 31/36 tumors with a median of three mutations per sample (range: 1–13). The only recurrent mutations have been observed in GNAS (31.4% of cases). However, seven genes involved in cAMP signaling pathway were affected in 14 of 36 samples and eight samples harbored variants in genes involved in the calcium signaling or metabolism. At the enrichment analysis, several altered genes resulted to be associated with developmental processes. No significant correlation between genetic alterations and the clinical data was observed. Conclusion: This study provides a comprehensive analysis of somatic mutations in a large series of GH-secreting adenomas. No novel recurrent genetic alterations have been observed, but the data suggest that beside cAMP pathway, calcium signaling might be involved in the pathogenesis of these tumors.